Sikap Profesional Dan Loyalitas Kerja Perawat Di Masa Pandemi Covid-19 (HEALTH CARE: JURNAL KESEHATAN, 2023)
ABSTRACTThe condition of the COVID-9 pandemic is a formidable challenge for nurses where nurses have a high risk of contracting COVID-19. Nurses keep going to work, completing their duties in caring for patients responsibly as a form of high nurse work loyalty. On the other hand, nurses also have a professional obligation to care for patients in various conditions, including during the COVID-19 pandemic. This study was to determine the relationship between professional attitude and work loyalty of nurses during the COVID-19 pandemic. The research design was correlational with a cross sectional approach. The population was 48 nurses and with the total sampling technique, a sample of 48 respondents is obtained. The independent variable  was professional attitude and the dependent variable was nurse job loyalty. Measuring tool using a questionnaire from each variable. Data were analyzed by Spearman's rho test with α